2020
DOI: 10.2174/1381612826666200115095937
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Dysregulated Signaling Pathways in Cancer

Abstract: Cancer cell biology takes advantage of identifying diverse cellular signaling pathways that are disrupted in cancer. Signaling pathways are an important means of communication from the exterior of cell to intracellular mediators, as well as intracellular interactions that govern diverse cellular processes. Oncogenic mutations or abnormal expression of signaling components disrupt the regulatory networks that govern cell function, thus enabling tumor cells to undergo dysregulated mitogenesis, to resist apoptosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 300 publications
0
15
0
Order By: Relevance
“…It was found that TE inhibited the viability of U87 cells more profoundly as compared to the normal astrocytes. This selective inhibition of U87 cells by TE could be attributed to the fact that several signalling pathways show dysregulation in cancer cells [19], and TE extract might modulate any of these pathways. However, more studies are needed to infer the exact mechanism for the selective inhibition of the U87 cells.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that TE inhibited the viability of U87 cells more profoundly as compared to the normal astrocytes. This selective inhibition of U87 cells by TE could be attributed to the fact that several signalling pathways show dysregulation in cancer cells [19], and TE extract might modulate any of these pathways. However, more studies are needed to infer the exact mechanism for the selective inhibition of the U87 cells.…”
Section: Discussionmentioning
confidence: 99%
“…9e). The defects of these pathways are reflected in the pathogenesis of various types of tumors including bladder cancer [38]- [40].…”
Section: E the Prognostic Signatures Of Mrmsmentioning
confidence: 99%
“…The disruption of pathway regulation by oncogenic mutations or the abnormal expression of key genes promotes tumor onset and progression. As for other kind of tumors, the identification of ES targetable molecular markers and their potential inhibitors will be useful for the development of tailored therapeutic regimens [ 22 ]. In this regard, an overexpression of VEGF (vascular endothelial growth factor), an important signaling protein involved in the angiogenesis pathway, has been reported in ES [ 23 ].…”
Section: Introductionmentioning
confidence: 99%